Strategi Komunikasi Badan Kepegawaian Dan Pengembangan Sumber Daya Manusia Dalam Digitalisasi Pelayanan Kenaikan Pangkat Pegawai Negeri Sipil - Rizal Fahmi; Mazdalifah; Syafruddin Pohan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The research uses a qualitative research approach with case study methods to analyze problems related to communication strategies formulated by organizations. The research results indicate that the communicators chosen to convey messages to the target audience have credibility, the message has been designed in such a way, the channel used is a personal channel face-to-face through technical guidance and consultation and by using the media but the media utilization is still not optimal and unable to reach the overall target audience. The communicant is all civil servants in the Pidie Jaya Regency Government and the effects are limited to changes in knowledge and changes in attitudes. Obstacles in delivering messages are found both in the communicator and the communicant, namely barriers in the delivery process (process barriers), semantic barriers (semantics barriers), and psycho-social barriers (psychosocial barriers) caused by the culture that is already attached to the audience, communicators and communicants are trying to overcome these various obstacles by using personal communication channels both face-to-face and through the media.